LESSONS FROM COVID-19: SMALL AND FINANCIALLY STRONG FAMILY - Thomas Soseco (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Households should small and but financially strong, especially to deal with a crisis where most families face a reduction in income but relatively constant expenditure. To maintain the standard of living, they need a buffer, measured from net wealth, i.e. total value of assets deducted by debts. There is no justification for how small the family size should be. For most households, higher net wealth is achieved when they have smaller household size, while only the poorest and richest households can get benefits from additional household members. However, we should also aware of the pseudo-increase of net wealth, i.e. households obtain an increasing net wealth because of additional household members but unable to push them to higher decile.